Optimal income taxation with tax competition - Vilen Lipatov; Alfons J. Weichenrieder (Center for Economic Studies and ifo Institute (CESifo), 2010)
We introduce tax competition for mobile labor into an optimal-taxation model with two skill levels. We analyze a symmetric subgame-perfect Nash equilibrium of the game between two governments and two taxpayer populations. Tax competition reduces the distortion from the informational asymmetry and increases employment of the less productive individuals. When countries are heterogeneous, this effect is more pronounced in the smaller country.
Keywords: F22; H21; 330; optimal income tax; migration; unemployment; tax competition; Leviathan government; Einkommensteuer; Steuerwettbewerb; Optimale Besteuerung; Internationale Arbeitsmobilität; Qualifikation; Spieltheorie; Nash-Gleichgewicht; Leviathan-Modell; Beschäftigungseffekt; Theorie